MODELING OF STRATEGIC POSITIONING OF THE ENTERPRISE ON THE BASIS OF INNOVATIVE DEVELOPMENT - KOSTENIUK, Yuliia; KRYVORUCHKO, Dariia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The paper analyzes the structure of the market share of revenues in the mobile communications market, focusing on changing trends, the impact of innovative technologies on the company's financial performance, also pays attention to the analysis of the number of users of PrJSC Kyivstar, substantiates the factors influencing changes in the number of users, which is an important indicator of the effectiveness of strategies aimed at attracting and retaining customers. The influence of the number of users on the financial indicators of net profit from the sale of services is determined, which allows to assess the financial stability and profitability of the company in a turbulent environment associated with the martial law in Ukraine and the occupation of territories. For a deeper analysis of the strategic positioning of the enterprise, the modified SPACE-analysis method and SWOT-analysis were applied. SWOT analysis allows to identify the strengths and weaknesses of the organization, as well as opportunities and threats from the external environment and takes into account the specifics of innovation processes, such as the introduction of new technologies, changes in consumer needs, new market opportunities and changes in the direction of specialization.To develop the SPACE model, the main factor was the high level of technological development of the company, which is the basis for Kyivstar's leading position in the market, so a model for developing the strategic direction of the enterprise's development based on a modified SPACE analysis matrix was proposed. SPACE-analysis is an important tool in assessing the strategic position and actions, which includes a reflection of external factors (attractiveness and sustainable scientific and technical development of the mobile communications industry) and internal factors (investment and innovation potential of the company). This methodology is used to evaluate strategic plans and processes, which is complemented by a SWOT analysis, which ultimately determines the strategic position of PrJSC Kyivstar in the oligopoly mobile market in Ukraine. The article is a useful resource for specialists in the field of strategic management and analysis of the telecommunications market, as well as for anyone interested in innovative business development in the context of globalization and digitalization.
Keywords: innovation; innovative development; strategy; modeling; strategic analysis; SWOT analysis; modified method SPACE